Wavelet‐Based Adaptive Computations of the Excitonic Eigenstates of Disordered Semiconductor Quantum Wires - Meier, Torsten; Mollet, Christian; Kunoth, Angela (AIP Conference Proceedings)
A novel adaptive wavelet based method is presented that allows us to compute eigenvalues and eigenvectors of the electronic Schrödinger equation. Our method outperforms direct discretization methods with equidistant grid spacings, in particular, for problems that involve several length scales. As an application we present numerical evaluations of the energetically lowest exciton states for ordered and disordered semiconductor quantum wires.

Theoretical approach to the ultrafast nonlinear optical response of metal slabs - Wand, Mathias; Schindlmayr, Arno; Meier, Torsten; Förstner, Jens (CLEO:2011 - Laser Applications to Photonic Applications)
We present an ab-initio method for calculating nonlinear and nonlocal optical effects in metallic slabs with sub-wavelength thickness. We find a strong localization of the second-harmonic current at the metal-vacuum interface.
Keywords: tet_topic_shg

High Performance Active Elements for Agricultural Machines Made of Ultra High-Strength Steels - Homberg, Werner; Rostek, Tim (Key Engineering Materials)
This article will highlight various aspects of the production process of high performance active elements made of ultra high-strength steels. Focus is put on the processing of thick sheet metal regarding hot forming by means of punching, embossing, and forging processes as well as on thermo-mechanical treatment. Due to the material thickness of the semi-finished parts/blanks used and owing to the high strength of the materials (Rm > 2600 MPa) current production techniques and parameters from the field of thin sheet metal can only be limitedly be transferred and have therefore been specially investigated for this application.

Presshärten von Rohren und Profilen mittels formlos fester Stoffe - Mennecart, Thomas; Rostek, Tim; Witulski, Jörg; Brosius, Alexander; Takkaya, A. Erman; Homberg, Werner

High Performance Active Elements for Agricultural Machines Made of Ultra High-Strength Steels - Homberg, Werner; Rostek, Tim (Proceedings. of the 10th International Conference on Technology of Plasticity (ICTP))

Teaching & Learning Guide for: New Media, Web 2.0 and Surveillance - Fuchs, Christian (Sociology Compass)

New Media, Web 2.0 and Surveillance - Fuchs, Christian (Sociology Compass)

Preface - Fuchs, Christian (İletişimi anlamak (Understanding communication), 4th revised)

The Political Economy of Privacy on Facebook - Fuchs, Christian

The Political Economy of Privacy - Fuchs, Christian

Analysis of Existing Empirical Research Methods for Studying (Online) Privacy and Surveillance - Sevignani, Sebastian; Kreilinger, Verena; Allmer, Thomas; Fuchs, Christian

X-ray absorption near-edge spectroscopy investigation of the oxidation state of Pd species in nanoporous SnO2 gas sensors for methane detection - Wagner, T.; Bauer, M.; Sauerwald, T.; Kohl, C.-D.; Tiemann, Michael (Thin Solid Films)
We report the correlation of the aging of Pd-doped SnO2 methane sensors with the change of the oxidation state of Pd. Mesoporous SnO2 doped with palladium species was prepared and exposed to different gas mixtures at high temperature (600 °C) to simulate long term usage. After each exposure step a fraction of the sample was cooled down to “freeze” the current oxidation state of Pd which was then analyzed by X-ray Absorption Near-Edge Spectroscopy (XANES) using the 'white line' (i.e. the absorption peak corresponding to the transition from the 2p3/2 core level to unoccupied 4 d states) intensity of the L(III) edge as a probe for the oxidation state. The Pd oxidation state correlates with the response of the resistive SnO2 sensor to methane gas, as determined by measuring the gas response to different concentrations of methane. Samples treated with 5000 ppm methane in air show a significant reduction of Pd(II) to Pd(0), depending clearly on the carrier gas (synthetic air, pure nitrogen) and on the temperature (600 °C vs. 300 °C).

A High Temperature Capacitive Humidity Sensor Based on Mesoporous Silica - Wagner, Thorsten; Krotzky, Sören; Weiß, Alexander; Sauerwald, Tilman; Kohl, Claus-Dieter; Roggenbuck, Jan; Tiemann, Michael (Sensors)
Capacitive sensors are the most commonly used devices for the detection of humidity because they are inexpensive and the detection mechanism is very specific for humidity. However, especially for industrial processes, there is a lack of dielectrics that are stable at high temperature (>200 °C) and under harsh conditions. We present a capacitive sensor based on mesoporous silica as the dielectric in a simple sensor design based on pressed silica pellets. Investigation of the structural stability of the porous silica under simulated operating conditions as well as the influence of the pellet production will be shown. Impedance measurements demonstrate the utility of the sensor at both low (90 °C) and high (up to 210 °C) operating temperatures.

Micrometer-sized nanoporous tin dioxide spheres for gas sensing - Smått, J.-H.; Lindén, M.; Wagner, T.; Kohl, C.-D.; Tiemann, Michael (Sensors and Actuators B: Chemical)
We report the synthesis of mesoporous tin dioxide (SnO2) materials with well-defined particle morphology. The products consist of uniform spheres with a diameter of 5 μm. The spheres are hierarchically porous with two distinct pore modes of 5.0 nm and 52 nm, respectively. This special porosity is the result of a synthesis procedure which involves a ‘hard templating’ (nanocasting) process. The product forms an approximately homogeneous monolayer of spheres on a sensor substrate and shows promising response to methane gas with low cross-sensitivity to water. The structural properties and gas-sensing performance are compared with a mesoporous SnO2 material without defined morphology, prepared by a ‘soft templating’ procedure.

Photocatalytic ozone sensor based on mesoporous indium oxide: Influence of the relative humidity on the sensing performance - Wagner, T.; Hennemann, J.; Kohl, C.-D.; Tiemann, Michael (Thin Solid Films)
Mesoporous In2O3, synthesized by a nanocasting procedure, is used as a resistive gas sensor for ozone in very low concentrations (from 20 ppb to 2.4 ppm) at room temperature. Its sensing performance is substantially increased by illumination with blue light (460 nm, 2.7 eV). For low ozone concentrations the sensor response increases with increasing humidity. However, higher humidity also results in the occurrence of a saturation of the response at lower ozone concentrations; this is rationalized by assuming a poisoning of surface active sites by hydroxyl groups.

A Critical Contribution to Theoretical Foundations of Privacy Studies - Allmer, Thomas (Journal of Information, Communication & Ethics in Society)

Piezoelectric sensor array with evaluation electronic for counting grains in seed drills - Meyer zu Hoberge, S.; Hilleringmann, Ulrich; Jochheim, C.; Liebich, M. (IEEE Africon '11)

Die Rezeption der Kirchenmusik Anton Bruckners. Genese, Tradition und Instrumentalisierung des Vergleichs mit Giovanni Pierluigi da Palestrina - Höink, Dominik
Einen 'modernen Palestrina' nennt Max Auer den Komponisten Anton Bruckner und pointiert damit eine noch heute virulente Vorstellung, die den katholisch-frommen Bruckner auf einer Linie mit dem durch die Retterlegende glorifizierten und päpstlicherseits kanonisierten Ideal Giovanni Pierluigi da Palestrina sieht. Diese stil- und rezeptionsgeschichtliche Untersuchung richtet aus diachroner Perspektive den Blick auf Genese und Tradierung dieses Komponistenvergleichs vom 19. Jahrhundert bis in die Gegenwart. Im Zentrum steht dabei die Analyse des maßgeblichen wissenschaftlichen Bruckner-Schrifttums und seiner kontextuellen Verortung innerhalb der bisweilen höchst ideologisch aufgeladenen musikgeschichtlichen Diskurse. Ferner werden auf der Basis neuer Quellen die Kanonisierungsbestrebungen hochrangiger Vertreter der Bruckner-Gesellschaft im Rahmen der sogenannten 'Aktion Rom' ausgewertet, die für die Instrumentalisierung des Vergleichs von zentraler Bedeutung sind. Es folgt eine Analyse derjenigen Kompositionen, die in die Nähe des Palestrina-Stils gerückt wurden. Am Ende der Arbeit steht eine Neubewertung des Vergleichs auf der Grundlage der aus Rezeptionsgeschichte und Analyse gewonnenen Ergebnisse.

Injection currents in (110)-oriented GaAs/AlGaAs quantum wells: recent progress in theory and experiment - Duc, H. T.; Pochwala, M.; Förstner, Jens; Meier, Torsten; Priyadarshi, S.; Racu, A. M.; Pierz, K.; Siegner, U.; Bieler, M. (Ultrafast Phenomena in Semiconductors and Nanostructure Materials XV)
We experimentally and theoretically investigate injection currents generated by femtosecond single-color circularly-polarized laser pulses in (110)-oriented GaAs quantum wells. The current measurements are performed by detecting the emitted Terahertz radiation at room temperature. The microscopic theory is based on a 14 x 14 k • p band-structure calculation in combination with the multi-subband semiconductor Bloch equations. For symmetric GaAs quantum wells grown in (110) direction, an oscillatory dependence of the injection currents on the exciting photon energy is obtained. The results of the microscopic theory are in good agreement with the measurements.
Keywords: tet_topic_qw

Electron g-factor anisotropy in symmetric (110)-oriented GaAs quantum wells - Hübner, J.; Kunz, S.; Oertel, S.; Schuh, D.; Pochwała, M.; Duc, H. T.; Förstner, Jens; Meier, Torsten; Oestreich, M. (Physical Review B)
We demonstrate by spin quantum beat spectroscopy that in undoped symmetric (110)-oriented GaAs/AlGaAs single quantum wells, even a symmetric spatial envelope wave function gives rise to an asymmetric in-plane electron Land´e g-factor. The anisotropy is neither a direct consequence of the asymmetric in-plane Dresselhaus splitting nor a direct consequence of the asymmetric Zeeman splitting of the hole bands, but rather it is a pure higher-order effect that exists as well for diamond-type lattices. The measurements for various well widths are very well described within 14 × 14 band k·p theory and illustrate that the electron spin is an excellent meter variable for mapping out the internal—otherwise hidden—symmetries in two-dimensional systems. Fourth-order perturbation theory yields an analytical expression for the strength of the g-factor anisotropy, providing a qualitative understanding of the observed effects.
Keywords: tet_topic_qw

Microscopic theory of the extremely nonlinear terahertz response of semiconductors - Golde, D.; Kira, M.; Meier, Torsten; Koch, S.W. (physica status solidi (b))
The extreme nonlinear terahertz response of initially unexcited intrinsic semiconductor nanostructures is studied theoretically by solving extended semiconductor Bloch equations numerically. The coupled dynamics of intraband acceleration and multiphoton interband transitions leads to high-harmonic generation up to several tens of the exciting terahertz frequency. It is shown that the actual cut-off frequency is determined by the band structure and not by the excitation strength.

Singen im Gottesdienst - Eine empirische Untersuchung - Schroeter-Wittke, Harald; Heye, Andreas; Gembris, Heiner (Singen im Gottesdienst. Ergebnisse und Deutungen einer empirischen Untersuchung in evangelischen Gemeinden)

Religionssensible Schulkultur

Die Zukunft der Orgel angesichts der Vielfalt christlicher Gottesdienste - Gemeindekulturpädagogische Beobachtungen - Schroeter-Wittke, Harald (Die Orgel zwischen gestern und morgen)

Singen im Gottesdienst. Ergebnisse und Deutungen einer empirischen Untersuchung in evangelischen Gemeinden

Überzeichnet - Religion in Comics

Simsalabimbambasaladusalasim. Zwischenbilanz einer Performativen Religionspädagogik - Schroeter-Wittke, Harald (Zeitschrift für Pädagogik und Theologie)

Motion and Emotion. Theologische Overtüre zum Thema Tanz und Religion - Schroeter-Wittke, Harald (Magazin für Theologie und Ästhetik. http://www.theomag.de/70/hsw13.htm)

Sexagesimae. 2Kor (11,18.23b-30) 12,1-10: Karneval mit Paulus - Eine Zuspitzung - Schroeter-Wittke, Harald (Göttinger Predigtmeditationen)

6. Sonntag nach Trinitatis. 5. Mose 7,6-12: Keine Kleinigkeit, oder: Wem die Phantasie durchgeht - Schroeter-Wittke, Harald; Kirsner, Inge (Predigtstudien III/2)

Popkultur als Herausforderung für die Kirchenmusik - Schroeter-Wittke, Harald (Liturgie und Kultur)

Gleichnis der Welt in Tönen. Zum 100. Todestag von Gustav Mahler - Schroeter-Wittke, Harald (Praktische Theologie)

Carla's Christmas Carols. Carla Bleys unorthodoxe Weihnacht - Schroeter-Wittke, Harald (Praktische Theologie)

Protestsongs.de - Schroeter-Wittke, Harald (Praktische Theologie)

"So reden wir immer!". Der Einfluss der Medien auf das Sprachverhalten junger Migranten in Deutschland - Günesli, Habib (tv diskurs)
Neue Medien eröffnen neue Möglichkeiten der Kommunikation und bringen neue sprachliche Erscheinungsformen zutage. Im Rahmen seiner Wissenschaftlichen Hausarbeit für die Erste Staatsprüfung für das Lehramt an Grund- und Hauptschulen hat sich der Autor mit dem Mediennutzungsverhalten und dessen Auswirkung auf die Sprachkompetenz junger türkischer Migranten beschäftigt.

Photocurrents in semiconductor carbon nanotubes with spin-orbit interaction - Meier, Torsten; Liu, Hong; Duc, Huynh Thanh; Schumache, Stefan (75. Annual meeting of the DPG and combined DPG Spring meeting)
In recent years, single-walled carbon nanotubes (SWCNTs) have received widespread attention due to their perfect quasi-one-dimensional structure and unique physical properties, as well as their potential for applications. In the present work, we calculate the band structure of SWCNTs using an atomistic tight-binding model including spin-orbit interaction. We combine this approach with a many-particle calculation of the nonlinear optical response using multi-band semiconductor Bloch equations. We show that, for SWCNTs lacking inversion symmetry, the intrinsic spin-orbit interaction can give rise to single-color photoinduced charge and spin currents. In particular, we study the influence of excitonic effects on these photoinduced currents and draw the analogy to recent investigations on single-color injection of photocurrents in semiconductor quantum wells.

Analysis of multidimensional Fourier transform spectroscopy for semiconductors with a phenomenological level model - Meier, Torsten; Wiebeler, Christian; Reichelt, Matthias (75. Annual meeting of the DPG and combined DPG Spring meeting)
Optical two-dimensional Fourier transform spectroscopy has been used to study the properties of semiconductor nanostructures in four-wave-mixing like experiments. Applying a phenomenological level model, we numerically and analytically analyze the main features of excitonic and biexcitonic contributions in a semiconductor quantum well by solving the optical Bloch equations. The method is extended to three-dimensional Fourier transform spectroscopy to investigate a recent experiment.

Extreme nonlinear optics in semiconductors with shaped laser pulses - Meier, Torsten; Reichelt, Matthias; Walther, Andrea (75. Annual meeting of the DPG and combined DPG Spring meeting)
If a two-level system is excited with an intense light field of several times the Rabi frequency, the well-known Mollow triplets appear in the emitted radiation spectrum. We show that the pattern of the emission spectrum can be changed by using appropriately shaped laser pulses. The effect is also observable for a more realistic description of a semiconductor system.

„Kutte & Co.“ – Zur textilen SchriftBildlichkeit des Heavy Metals - Eckel, Julia (Metal Matters – Heavy Metal als Kultur und Welt)

Tilting on non–commutative rational projective curves - Burban, Igor; Drozd, Yu. (Mathematische Annalen)

Mars-Viskurse. De- und Re-Kontextualisierungen von wissenschaftlichen Bildern - Adelmann, Ralf (Blickregime und Dispositive audiovisueller Medien)

Von der Freundschaft in Facebook - Adelmann, Ralf (Generation Facebook. Über das Leben im Social Net)

"Oh, Oh, Oh, let's count some more." Hochschulrankings als mediale Form - Adelmann, Ralf (Zeitschrift für Medienwissenschaft 1/2011)

Supportive and hindering factors to a sustainable implementation of ICT in schools - Eickelmann, Birgit (Journal for Educational Research Online/Journal für Bildungsforschung Online)

Restructuring educational systems to move into the digital age. Report of EduSummIT 2011 - Davis, Niki; Eickelmann, Birgit; Schulz-Zander, Renate (International Summit of ICT in Education: Building a Global Community of Policy-Makers, Educators, and Researchers to Move Education into the Digital Age)

Wirkungen digitaler Medien - Herzig, Bardo; Grafe, S. (Schule in der digitalen Welt. Medienpädagogische Ansätze und Schulforschungsperspektiven)

Medienkompetenz – Grundbegriffe, Kompetenzmodelle, Standards. - Herzig, Bardo; Grafe, S. (Kompetenzorientierung in Schule und Lehrerbildung. Perspektiven der bildungspolitischen Diskussion, der Bildungsforschung und der Mathematik-Didaktik)

Zukunftsfähige Lernkultur - Herzig, Bardo; Grafe, S. (Bildung Spezial. Friedrich Jahresheft 3/2011)

Religionssensible Schulkultur aus erziehungswissenschaftlicher Sicht - Freitag, Christine (Religionssensible Schulkultur)

Anpassen, verändern, abschaffen? Schulische Leistungsbewertung in der Diskussion

Wie muss die schulpraktisch orientierte Lehrerbildung die schulischen Veränderungen aufnehmen? - Freitag, Christine (Schulpraxisstudien in Europa)

How Hydrogen Bonds Influence the Mobility of Imidazolium-Based Ionic Liquids. A Combined Theoretical and Experimental Study of 1-n-Butyl-3-Methylimidazolium Bromide - Kohagen, M.; Brehm, Martin; Lingscheid, Y.; Giernoth, R.; Sangoro, J.; Kremer, F.; Naumov, S.; Iacob, C.; Kärger, J.; Valiullin, R.; Kirchner, B. (J. Phys. Chem. B)

Performance of Quantum Chemically Derived Charges and Persistence of Ion Cages in Ionic Liquids. A Molecular Dynamics Simulations Study of 1-n-Butyl-3-Methylimidazolium Bromide - Kohagen, M.; Brehm, Martin; Thar, J.; Zhao, W.; Müller-Plathe, F.; Kirchner, B. (J. Phys. Chem. B)

Singular Value Decomposition for Analyzing Temperature- and Pressure-Dependent Radial Distribution Functions: Decomposition into Grund RDFs (GRDFs) - di Dio, P. J.; Brehm, Martin; Kirchner, B. (J. Chem. Theory Comput.)

Ab initio Molecular Dynamics Simulations of a Binary System of Ionic Liquids - Brüssel, M.; Brehm, Martin; Voigt, T.; Kirchner, B. (Phys. Chem. Chem. Phys.)

TRAVIS – A Free Analyzer and Visualizer for Monte Carlo and Molecular Dynamics Trajectories - Brehm, Martin; Kirchner, B. (J. Chem. Inf. Model.)

Produktionsverfahren zur Herstellung höchstfester hybrider Leichtbaustrukturen für den Einsatz im Automobil - Lauter, Christian; Damerow, Ulf; Frantz, Meike; Tröster, Thomas; Homberg, Werner

Manufacturing processes for automotive structures in multi-material design consisting of sheet metal and CFRP prepregs - Lauter, Christian; Dau, J.; Tröster, Thomas; Homberg, Werner

Multi-material systems. High strength steels and fiber-reinforced plastics - Lauter, Christian; Sköck-Hartmann, Britta; Gries, Thomas; Tröster, Thomas; Linke, Markus

Hybrid FRP-Steel components for automotive applications - Kochanek, C.; Siewers, Bernd; Frantz, Meike; Glowania, M.; Linke, M.; Lauter, Christian; Gries, Thomas; Tröster, Thomas

Multi-material systems for tailored automotive structural components - Dau, J.; Lauter, Christian; Damerow, U.; Homberg, Werner; Tröster, Thomas

Kindheitskonzepte in islamischer Perspektive. Ein Streifzug - Tatari, Muna; Isik-Yiğit, Tuba (Religionssensible Schulkultur)

Zur Wirkung der Lehrerbildung: Stand und Perspektiven am Beispiel der Physik - Riese, Josef; Vogelsang, Christoph; Reinhold, Peter (Kompetenzorientierung in Schule und Lehrerbildung aus den Perspektiven der Bildungspolitik, der empirischen Bildungsforschung und der Mathematik-Didaktik)

Modellierung fachwissenschaftlicher Kompetenz angehender Physiklehrkräfte. - Woitkowski, David; Riese, Josef; Reinhold, Peter (Zeitschrift für Didaktik der Naturwissenschaften)

Parameter Identification of Constitutive Models for Fluidsaturated Porous Media within an FE-Setting - Mahnken, Rolf; Steinmann, P. (ZAMM - Journal of Applied Mathematics and Mechanics / Zeitschrift für Angewandte Mathematik und Mechanik)
Keywords: Applied Mathematics; Computational Mechanics

Numerical Simulation of Interface Debonding during Fibre Pull-Out Tests - Döbert, C.; Mahnken, Rolf; Stein, E. (ZAMM - Journal of Applied Mathematics and Mechanics / Zeitschrift für Angewandte Mathematik und Mechanik)
Keywords: Applied Mathematics; Computational Mechanics

Improvements for finite-element implementation of the Gurson Model - Mahnken, Rolf (ZAMM - Journal of Applied Mathematics and Mechanics / Zeitschrift für Angewandte Mathematik und Mechanik)
Keywords: Applied Mathematics; Computational Mechanics

Professionelle Handlungskompetenz zukünftiger Physiklehrkräfte - Korneck, Friederike; Lamprecht, Jan; Oettinghaus, Lars; Reinhold, Peter; Riese, Josef; Vogelsang, Christoph; Woitkowski, David (Naturwissenschaftliche Bildung als Beitrag zur Gestaltung partizipativer Demokratie. Gesellschaft für Didaktik der Che-mie und Physik. Jahrestagung in Potsdam 2010)

Erfassung der professionellen Kompetenz von Lehramtsstudierenden - Rehm, Markus; Bölsterli, Katrin; Brovelli, Dorothee; Kauertz, Alexander; Reinhold, Peter; Riese, Josef; Wilhelm, Markus (Naturwissenschaftliche Bildung als Beitrag zur Gestaltung partizipativer Demokratie. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Potsdam 2010)

Kompetenzniveaus beim Fachwissen angehender Physiklehrkräfte - Woitkowski, David; Riese, Josef; Reinhold, Peter (Naturwissenschaftliche Bildung als Beitrag zur Gestaltung partizipativer Demokratie. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Potsdam 2010)

Die Wirksamkeit verschiedener Lehramtsstudiengänge Physik im Vergleich - Riese, Josef; Reinhold, Peter (Naturwissenschaftliche Bildung als Beitrag zur Gestaltung partizipativer Demokratie. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Potsdam 2010)

Quereinsteiger in das Lehramt Physik in der Sekundarstufe 1 - Oettinghaus, Lars; Korneck, Friederike; Lamprecht, Jan; Riese, Josef (PhyDid B, Didaktik der Physik, Beiträge zur DPG-Frühjahrstagung 2011 in Münster)

Unterschiede im Professionswissen bei angehenden Physiklehrkräften – Ein Vergleich verschiedener Lehramtszugänge - Riese, Josef; Gramzow, Yvonne; Reinhold, Peter; Oettinghaus, Lars; Korneck, Friederike (PhyDid B, Didaktik der Physik, Beiträge zur DPG-Frühjahrstagung 2011 in Münster)

Wissensbasierte Kompetenzprofile angehender Physiklehrkräfte - Gramzow, Yvonne; Riese, Josef; Reinhold, Peter (PhyDid A - Physik und Didaktik in Schule und Hochschule)
Um die Qualität der Ausbildung von Lehrkräften beurteilen zu können, wurden in den letzten Jahren verschiedene Untersuchungen zur Kompetenzmodellierung und Kompetenzmessung bei Lehramtsstudierenden und Lehrkräften initiiert. Im Zusammenhang mit möglichen Maßnahmen zur Verbesserung der Lehrerausbildung wird dabei auch über bedarfsgerechte und individualisierte Fördermaßnahmen gesprochen. Als erster Schritt auf diesem Weg kann eine Typenbildung in der Gruppe der Lehramtsanwärter dazu dienen, eine gezielte Binnendifferenzierung vorzunehmen. Vor diesem Hintergrund wurden in der vorgestellten Analyse die Daten einer bundeslandübergreifenden Kompetenzmessung bei Lehramtsstudierenden der Physik dazu genutzt, eine Typisierung auf der Grundlage der gemessenen Leistungen in den drei Bereichen des Professionswissens von Physiklehrkräften (Fachwissen, fachdidaktisches Wissen, allgemeines pädagogisches Wissen) durchzuführen. Dabei konnten drei unterschiedliche Kompetenzprofile identifiziert werden: ein fachenthusiastisches Profil, ein schulpraktisch orientiertes Profil und ein leistungsschwaches Profil. Die identifizierten Profile werden im Weiteren anhand demographischer Daten, Beliefs und motivationaler Orientierungen charakterisiert, so dass die Ergebnisse als Anknüpfungspunkt genutzt werden könnten, um künftig eine stärkere Individualisierung der Lehrerausbildung speziell im Fach Physik zu realisieren.

Freies Spiel beobachten. Chancen und Stolpersteine - Bruns, Julia; Eichen, L.; Pfiffner, M.; Walter-Laager, C. (gruppe & spiel)

Geschlechterforschung. Theorien, Thesen und Themen zur Einführung.
Das Studienbuch gibt einen einführenden Überblick zum Stand der Geschlechterforschung in verschiedenen Disziplinen. Es eröffnet grundlegende Einblicke zum aktuellen Stand der Diskussion, erörtert zentrale und spezifische Fragestellungen und folgt der Geschichte der Geschlechterdebatte in den verschiedenen wissenschaftlichen Fächern. Dabei finden neben den Sozial- und Geisteswissenschaften auch die Natur- und Technikwissenschaften ausführliche Berücksichtigung. Das Buch erschöpft sich dabei nicht in einer Bestandsaufnahme, sondern greift beispielhaft aktuelle Forschungs- und Fragestellungen auf, die ein Licht werfen auf die beeindruckende Themenvielfalt, die ergebnisreichen Einsichten, aber auch die zukünftigen Aufgaben der Geschlechterforschung. Das Glossar am Ende des Bandes erläutert die wichtigsten Begriffe aus dem Bereich der Geschlechterforschung und verweist auf hilfreiche weiterführende Literatur.

Jungenpädagogik im Widerstreit
Seit längerem wird in der pädagogischen Fachliteratur der Befund diskutiert, dass Mädchen im Bildungssystem erfolgreicher sind als Jungen. Wie ist dieses Phänomen zu erklären? Hat die Pädagogik die Grenzen und Unterschiede zwischen den Geschlechtern unterschätzt? Die Debatte über Jungen und ihre Probleme ist von einer stark vereinfachenden Gewinn-Verlust-Rechnung und einer dramatisierenden Tonlage gekennzeichnet, die die Komplexität des Themas eher verdecken als aufzuklären vermögen. Ziel des Buches ist es, aus unterschiedlichen Blickwinkeln den aktuellen internationalen Forschungsstand und die thematischen Brennpunkte der aktuellen Jungendebatte zu erörtern. Daraus werden schließlich Perspektiven für eine kritische Pädagogik der Geschlechter für Jungen und Mädchen entwickelt.

Intercultural Competence among Sports and PE Teachers. Theoretical Foundations and Empirical Verification - Grimminger-Seidensticker, Elke (European Journal of Teacher Education)

Zum Umgang mit Heterogenität im Sportunterricht. Die Bedeutsamkeit von Genderkompetenz und Interkultureller Kompetenz von Sportlehrkräften - Grimminger-Seidensticker, Elke; Frohn, J. (Empirie des Schulsports: Forschungsstand und Befunde)

Die Erfahrung von Anerkennung und Zugehörigkeit im Schulsport. Empirische Befunde und sportpädagogische Differenzierungen - Grimminger-Seidensticker, Elke; Gieß-Stüber, P. (Sportpädagogik als Erfahrungswissenschaft)

Anerkennungs- und Missachtungskulturen von Mädchen und Jungen im Sportunterricht - Grimminger-Seidensticker, Elke (Geschlecht und bewegungsbezogene Bildung(sforschung))

Application of the Discontinuous Galerkin Time Domain Method to the Optics of Bi-Chiral Plasmonic Crystals - Grynko, Yevgen; Förstner, Jens; Meier, Torsten; Radke, André; Gissibl, Timo; Braun, Paul V.; Giessen, Harald
A simulation environment for metallic nanostructures based on the Discontinuous Galerkin Time Domain method is presented. It is used to model optical transmission by silver bi‐chiral plasmonic crystals. The results of simulations qualitatively and quantitavely agree with experimental measurements of transmitted circular polarization.
Keywords: tet_topic_meta

Virtual tester development using HDL/PLI - Kamran, Arezoo; Nemati, Nastaran; Sadeghi-Kohan, Somayeh; Navabi, Zainalabedin (2010 East-West Design & Test Symposium (EWDTS))

Synthesis of highly stable magnesium fluoride suspensions and their application in the corrosion protection of a Magnesium alloy - Waltz, Florian; Swider, Mark A.; Hoyer, Kay-Peter; Hassel, Thomas; Erne, Martin; Möhwald, Kai; Adlung, Matthias; Feldhoff, Armin; Wickleder, Claudia; Bach, Friedrich-Wilhelm; Behrens, Peter (Journal of Materials Science)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

The ‘German Nation’ and the ‘black Other’: Social Darwinism and the cultural mission in German colonial discourse - Schubert, Michael (Patterns of Prejudice)

French, Belgian, British and US Occupation Troops in Western and Southwestern Germany 1918-1930 - Schubert, Michael (The Encyclopedia of Migration and Minorities in Europe. From the 17th Century to the Present)

(the ActiFE Study Group). Walking on sunshine: effect of weather conditions on physical activity in older people - Klenk, J.; Büchele, G.; Rapp, K.; Franke, Sebastian; Peter, R. (Journal of Epidemiology and Community Health. JECH Online First, published on February 15, 2011)

Assessing the long-term effect of industrial services on firm profitability: The moderating impact of product innovations (ausgezeichnet mit Best Overall Conference Paper Award) - Eggert, A.; Hogreve, J.; Ulaga, W.; Münkhoff, Eva (2011 AMA Winter Academic Conference, Austin, TX)

Service orientation of manufacturing companies: A necessary or sufficient condition for firm profitability? - Eggert, A.; Münkhoff, Eva; Thiesbrummel, C. (40th EMAC Annual Conference, Ljubljana)

Time extension of sales promotions – How do customers react? - Münkhoff, Eva; Garnefeld, I.; Bruns, A. (40th EMAC Annual Conference, Ljubljana)

Industrial services, product innovations, and firm profitability: A multiple-group latent growth curve analysis - Eggert, Andreas; Hogreve, Jens; Ulaga, Wolfgang; Münkhoff, Eva (Industrial Marketing Management)
Keywords: Marketing

Die unbewusste Wahrnehmung einer Wurftäuschung im Handball - Güldenpenning, Iris; Machlitt, Daniel; Schack, Thomas (Abstracts of the 53nd Conference of Experimental Psychologists (TeaP))

Die Rolle motorischer Expertise in der Bewegungswahrnehmung: Eine EEG-Studie - Koester, Dirk; Güldenpenning, Iris; Schack, Thomas (Abstracts of the 53nd Conference of Experimental Psychologists (TeaP))

Experimentelle Untersuchungen zur zeitlichen Ordnung mentaler Repräsentationen - Güldenpenning, Iris; Koester, Dirk; Schack, Thomas (Embodiment: Wahrnehmung-Kognition-Handlung. Tagung der dvs-Sektion Sportmotorik)

Bewegungspriming des Angriffsverhaltens im Volleyball - Frantzen, Christian; Güldenpenning, Iris; Schack, Thomas (Embodiment: Wahrnehmung-Kognition-Handlung. Tagung der dvs-Sektion Sportmotorik)

Wahrnehmung einer Täuschungshandlung im Beachvolleyball - Steinke, A; Güldenpenning, Iris; Schack, Thomas (Embodiment: Wahrnehmung-Kognition-Handlung. Tagung der dvs-Sektion Sportmotorik)

Erkennen von Finten auf Grundlage unbewusster Reize? - Machlitt, Daniel; Güldenpenning, Iris; Schack, Thomas (Embodiment: Wahrnehmung-Kognition-Handlung. Tagung der dvs-Sektion Sportmotorik)

Verarbeitung komplexer Bewegungen: Eine EEG-Studie - Koester, Dirk; Güldenpenning, Iris; Schack, Thomas (Embodiment: Wahrnehmung-Kognition-Handlung. Tagung der dvs-Sektion Sportmotorik)

Chunking and categorization in motor memory? Experimental studies in free climbing - Schack, Thomas; Güldenpenning, Iris (Sport and Exercise Psychology: Human Performance, Well-being and Health: Proceedings of the 13th FEPSAC European Congress of Sport Psychology)

Motor expertise modulates the unconscious processing of human body postures - Güldenpenning, Iris; Koester, Dirk; Kunde, Wilfried; Weigelt, Matthias; Schack, Thomas (Experimental Brain Research)